Pengembangan Sistem Informasi Manajemen dan Prediksi Permintaan Pemesanan Bibit Parfum Pada Toko Blossom Perfume Berbasis Web - Fachrur Rozy; Faizatul Amalia; Randy Cahya Wihandika (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Business people use many technological developments in their business, one of which is the management information system. The perfume business is a business that is available in various regions. Blossom Perfume is a shop that runs a famous perfume business in the Kisaran area, Asahan Regency, North Sumatra. Blossom Perfume is currently still using manual methods in transaction data and checking the stock of perfume seeds at each outlet as well as the estimated demand for seed stock in the following month. To solve this problem, a management information system was developed that supports Blossom Perfume in writing sales transactions and optimizing information. The development process in this system uses the waterfall model method. The main features contained in this management system are adding transaction data, viewing transaction history, viewing seed stock at each outlet and predicting orders for perfume seeds. This system is expected to make it easier for owners to manage their business. In making predictions, this system uses the Single Exponential Smoothing (SES) method. The choice of this algorithm is because it requires little past data by assuming fluctuations in data around the average value that still pay attention to patterns or trends. Web-based system with Codeigniter (CI) framework. Testing on this system uses the Whitebox method for unit testing and integration and the Blackbox method for testing validation. Reusability testing was also carried out using the System Usability Scale (SUS) method with a final score of 88.3 (acceptable).